R&D Subsidies and the Surplus Appropriability Problem - Anders Sørensen (Copenhagen Business School (CBS), Department of Economics, 2005)
It may be optimal from a welfare perspective to use R&D subsidies when the source of R&D distortions originates from the surplus appropriability problem and technological spillovers in the form of knowledge spillovers, creative destruction, and duplication externalities are absent. Hence, R&D subsidies may constitute the optimal policy even when subsidies directly targeted on monopoly pricing could be applied. The result holds when dynamic effects are important relative to static effects and when governments spending is restricted. The latter characteristic arises when a government is unable or unwilling to use the level of spending required to implement the optimum policy. The argument is developed in a semi-endogenous growth model where the only distortion is monopoly pricing of intermediate goods.
hdl:10398/7541
Keywords: O38; O41; 330; R&D; policy instruments; welfare; market power